Analysis on precise intermodulation product computing technique and reduction of computational load - Gan, Woon-Seng (2013)
In this paper, a modified version of precise intermodulation technique is presented with detailed mathematical analysis. The modified technique can reduce the computational growth of the original technique by 25-50% while obtaining the same results. The main idea is based on exploitation of triangular symmetric pattern in polynomials.